Complementary and Alternative Medicine Use in African Americans With Rheumatoid Arthritis12. Issue 2 (February 2014) - Tamhane, Ashutosh; McGwin, Gerald; Redden, David T.; Hughes, Laura B.; Brown, Elizabeth E.; Westfall, Andrew O.; Conn, Doyt L.; Jonas, Beth L.; Smith, Edwin A.; Brasington, Richard D.; Moreland, Larry W.; Bridges, S. Louis; et al.
<x xml:space="preserve">Abstract</x> Objective Racial/ethnic differences with regard to complementary and alternative medicine (CAM) use have been reported in the US. However, specific details of CAM use by African Americans with rheumatoid arthritis (RA) are lacking. Methods Data were collected from African Americans with RA enrolled in a multicenter registry regarding the use of CAM, including food supplements, topical applications, activities, and alternative care providers. Factors associated with CAM use by sex and disease duration were assessed using t‐test, Wilcoxon's rank sum test, chi‐square test, and logistic regression analyses. Results Of the 855 participants, 85% were women and mean age at enrollment was 54 years. Overall, ever using any of the CAM treatments, activities, and providers was 95%, 98%, and 51%, respectively (median of 3 for number of treatments, median of 5 for activities, and median of 1 for providers). Those with longer disease duration (>2 years) were significantly more likely (odds ratio ≥2.0, P < 0.05) to use raisins soaked in vodka/gin, to take fish oils, or to drink alcoholic beverages for RA treatment than those with early disease. As compared to men, women were significantly (P < 0.05) more likely to pray/attend church, write in a journal, and use biofeedback, but were less likely to smoke tobacco or topically apply household oils for treatment of RA. Conclusion CAM use was highly prevalent in this cohort, even in individuals with early disease. Health care providers need to be aware of CAM use as some treatments may potentially have interactions with conventional medicines. This could be important within this cohort of African Americans, where racial disparities are known to affect access to conventional care.